Can background baroque music help to improve the memorability of graphical passwords? - Gao, Haichang; Chang, Xiuling; Ren, Zhongjie; Aickelin, Uwe; Wang, Liming (Springer, 2010)
Graphical passwords have been proposed as an alternative to alphanumeric passwords with their advantages in usability and security. However,they still tend to follow predictable patterns that are easier for attackers to exploit,probably due to users’ memory limitations. Various literatures show that baroque music has positive effects on human learning and memorizing. To alleviate users’ memory burden, we investigate the novel idea of introducing baroque music to graphical password schemes (specifically DAS, PassPoints and Story) and conduct a laboratory study to see whether it is helpful. In a ten minutes short-term recall, we found that participants in all conditions had high recall success rates that were not statistically different from each other. After one week, the music group coped PassPoints passwords significantly better than the group without music. But there was no statistical difference between two groups in recalling DAS passwords or Story passwords. Further more, we found that the music group tended to set significantly more complicated PassPoints passwords but less complicated DAS passwords.